Rabinowitz Floer homology of negative line bundles and Floer Gysin sequence - Albers, Peter; Kang, Jungsoo (Advances in mathematics, 2023)
This article is concerned with the Rabinowitz Floer homology of negative line bundles. We construct a refined version of Rabinowitz Floer homology and study its properties. In particular, we build a Gysin-type long exact sequence for this new invariant and discuss an application to the orderability problem for prequantization spaces. We also construct a short exact sequence for the ordinary Rabinowitz Floer homology and provide computational results.